ORNITHINE TRANSCARBAMYLASE DEFICIENCY – THE REAL CAUSE OF “FAMILY CURSE”. A CASE REPORT - Zh. Sh. Bagomedova; A. S. Kotov; M. N. Borisova; M. V. Panteleeva; N. V. Zhurkova; A. A. Byome; Yu. Yu. Kotalevskaya; O. S. Mironova; I. V. Razheva (Русский журнал детской неврологии, 2016)
Ornithine transcarbamylase deficiency (type II hyperammonemia) – X-linked metabolic disorder of the urea cycle, caused by mutations of the gene encoding ornithine transcarbamylase (OTC). Changes to the nervous system caused by degenerative processes in the gray and white matter of the cerebral hemispheres. The authors describe 1-year-old boy with ornithine transcarbamylase deficiency as a clinical example, with the onset of the disease in the first year of life, with refusal of food, vomiting, weakness and tiredness progressing to lethargy and unconsciousness, convulsive seizures, refusal from meat in the interictal period, delayed of psychomotor development. The child was admitted to the children’s intensive care unit in serious condition, unconscious with severe neurological symptoms. The clinical picture, the results of instrumental and laboratory examination and the presence of family history were the basis for the assumption of the hereditary origin of the disease. Genetic further examination was planned. In the context of children’s intensive care unit, the patient was undergoing of intensive therapy, which had no effect. Death occurred on the 5th day of hospitalization. To verify the diagnosis post-mortem autopsy was conducted, based on which was installed the immediate cause of death. In confirming the diagnosis is considered as tandem mass spectrometry, and DNA diagnostics.